Teacher’s Strategies in Developing English Speaking Skills of Students With Intellectual Disabilities Trough Role-Play Activities: A Case Study - Rizki Tiara Ayunda; Benni Ichsanda Rahman Hz (Journal of Educational Sciences, 2026)
This study investigates teachers’ strategies for developing English speaking skills in students with intellectual disabilities using role-playing activities in an inclusive high school classroom. This study takes a qualitative approach, with a case study design centered on an 11th-grade student with an intellectual disability. Data were gathered through classroom observations, semi-structured interviews with the English teacher, field notes, and documentation. To increase the credibility of the findings, data were analyzed thematically using source triangulation. The findings show that the teacher used several key strategies, including providing meaningful communicative contexts through simplified role-play scenarios, scaffolding with modeling and cue cards, and consistently providing positive reinforcement during learning activities. The research findings also show that students’ speaking skills gradually improve, particularly in terms of participation, confidence in speaking, and willingness to use English in simple communication. Although linguistic improvements such as vocabulary, grammar, and pronunciation are limited, role-playing allows students to engage in more authentic and contextual communication practices. This study confirms that role-playing, when combined with adaptive learning strategies, can help to create a more inclusive learning environment and promote the development of speaking skills in students with intellectual disabilities.